(untitled) (Future Cities and Environment, 2025)
Livability includes similar understandings of sustainability, quality of life, character of a place, and public health. Can the livability of housing be maintained or increased? The purpose of this study is to develop factors of livability to improve sustainable settlements. This is descriptive research that describes an object and subject being studied without any engineering. The research variable is the formulation of factors for the level of living power of formal housing based on a literature search. The Descriptive Review method is used to obtain livability factors in supporting literature. Factors forming livability are (1). Physical residential units (2) Affordability of facility (3). Housing Amenities (4). Safety and security (5) Social interaction Community (6) Circular economy. Security and safety factors are the main criteria for shaping the adaptation of settled behavior in the face of climate change. Community social interaction factors are criteria for forming livability on a neighborhood scale. The results of this study contribute to the formation of adaptation of resilient settlement behavior to climate change. In addition, the results of this study can also be used as a guide in housing planning that is adaptive to climate change